Kinship Caregivers: Communicating with Children about a Parent’s Deployment - Elizabeth Thomas; Larry F. Forthun (EDIS, 2013)
The deployment of a military parent is undoubtedly a difficult time for children. This is especially true if the military child is being cared for by a relative, or kinship parent such as a grandparent, aunt, uncle, or older sibling. The child may have to experience a kind of personal deployment from their own home. To help children cope with these changes, it is important for the kinship parent to effectively communicate with the child about the deployment and the deployed parent. This will safeguard against emotional and behavioral problems and can lead to improvements in the child’s overall sense of well-being. This 3-page fact sheet was written by Elizabeth Thomas and Larry F. Forthun and published by the UF Department of Family Youth and Community Sciences, March 2013.